Morphometric Analysis to Infer Hydrological Behaviour of Lidder Watershed, Western Himalaya, India. (7th April 2013) - Altaf, Farrukh; Meraj, Gowhar; Romshoo, Shakil A.
Abstract : West Lidder River, in the Northwest Greater-Himalayan mountain range, is the major source of irrigation and drinking water supplies for the Kashmir Valley with a population of seven million people. The major source of water for the whole Lidder River is snow and icemelt emanating from its two subcatchments East Lidder and West Lidder. Snowmelt significantly contributes to the evolution of drainage patterns in this area. Quantitative morphometry plays a vital role in routing the snowmelt and other hydrological processes. Morphometric analysis of the West Lidder River catchment was carried out using geospatial technique. The outcome revealed that the entire study area has uniform lithology and is structurally permeable. The high drainage density of all subwatersheds indicate more surface runoff. The morphometric analysis also indicates that the area is more prone to weathering due to very-coarse to coarse drainage texture. All the subwatersheds showed dendritic to subdendritic drainage pattern. An immense control of structure on the drainage in some subwatersheds is indicated by their high bifurcation ratios. Circulatory and elongation ratios show that the subwatersheds have elongated to circular shapes. From the integrated analysis of the morphometric parameters, important hydrologic behaviour of 17 subwatersheds could be inferred.